Impact of Hydrodynamic Loads-Induced Blade Deflections on Tidal Turbine Performance (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy is gaining traction as a predictable renewable resource, particularly in the United Kingdom. However, tidal turbines operate in difficult environments, where the rotor blades are subjected to significant hydrodynamic loads. As the sector advances towards larger and more flexible rotors to maximise energy capture, these loads may result in notable blade deformations. This study investigates the effects of blade deflections induced by hydrodynamic loads on tidal turbine performance using a reference 1.6 m diameter rotor from the Tidal Turbine Benchmarking Project. Hydrodynamic loads were obtained from blade-resolved Reynolds-Averaged Navier-Stokes Computational Fluid Dynamics simulations, and used in a validated Finite Element model to compute flapwise and edgewise blade deflections. These deformations were mapped onto the blade geometry and introduced into a second set of flow simulations using a custom mesh motion function. The results show that moderate deflections have limited impact on power production while reducing spanwise bending moments, suggesting improved structural performance. These findings underscore the potential benefits of incorporating blade flexibility or intentional deformations into the design, allowing for lighter, more resilient, and cost-effective tidal turbine blades.